2012
DOI: 10.1111/j.1741-2358.2011.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Maximal voluntary tongue pressure is decreased in Japanese frail elderly persons

Abstract: Maximal voluntary tongue pressure is decreased in Japanese frail elderly personsBackground and objective: To quantitatively estimate tongue function, we developed a handy device for intraoral pressure measurement. The objective of this study was to assess maximum voluntary tongue pressure (MVTP) in Japanese frail elderly persons receiving nursing care services. Materials and methods: The study included 42 men and 87 women, aged 58-100 years. To record MVTP, the participants were asked to compress the balloon (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 16 publications
2
99
0
Order By: Relevance
“…However, this underestimation, in which only extreme decreases in skeletal muscle mass and power were examined, may have shown the relationship between sarcopenia and dysphagia. Finally, only a few studies have reported that ADL and nutritional status are associated with dysphagia [13,14,40,41,44]. Furthermore, only a handful of reports have mentioned the relationship between secondary sarcopenia and dysphagia [15,44].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, this underestimation, in which only extreme decreases in skeletal muscle mass and power were examined, may have shown the relationship between sarcopenia and dysphagia. Finally, only a few studies have reported that ADL and nutritional status are associated with dysphagia [13,14,40,41,44]. Furthermore, only a handful of reports have mentioned the relationship between secondary sarcopenia and dysphagia [15,44].…”
Section: Discussionmentioning
confidence: 97%
“…Although a decrease in maximum tongue pressure has been reported in elderly people [7][8][9][10][11][12], it is unclear what other factors are associated with a decrease in maximum tongue pressure. Tsuga et al [13] reported that activities of daily living (ADL), which was categorized into 4 classes according to the Japanese criteria for evaluating the degree of independence of disabled elderly subjects, was related to tongue pressure, and that elderly subjects with disability had significantly lower maximum tongue pressure. Although Tamura et al [14] did not examine tongue pressure, they reported the association between tongue thickness and mid-arm muscle area (AMA) as systemic nutritional status (correlation coefficient r = 0.424, p \ 0.001).…”
Section: Introductionmentioning
confidence: 99%
“…1B (a)) [14][15][16]. Participants were asked to compress the balloon of a disposable intraoral pressure probe upward onto their palates for 7 s using the maximum voluntary effort of the tongue (Fig.…”
Section: Mtp Measurementmentioning
confidence: 99%
“…The videofluoroscopic swallow study (VFS) is a classic technique that evaluates all four stages of the swallowing process [13]. In contrast, new digital apparatus for assessing maximal tongue pressure (MTP) can selectively evaluate the oral stage [14][15][16]. Furthermore, we have developed new equipment that can selectively assess the pharyngeal stage using impedance pharyngography (IPG) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several simple and non-invasive methods have been developed for evaluating swallowing function (Yoshikawa et al, 2011;Tsuga et al, 2012;Weikamp et al, 2012). Tongue sonography may be an objective and non-invasive swallowing evaluation technique that carries no risk of aspiration.…”
Section: Introductionmentioning
confidence: 99%